Expression and regulation of AC133 and CD133 in glioblastoma - Campos, Benito; Zeng, Lingcheng; Dao Trong, Huy Philip; Eckstein, Volker; Unterberg, Andreas; Mairbäurl, Heimo; Herold-Mende, Christel (Glia, 2011)
The biological significance of CD133 in glioblastoma is controversial. Above all, there is disagreement concerning the proper approach, the appropriate (cell) model and the suitable microenvironment to study this molecule, often leading to inconsistent experimental results among studies. In consideration of a primary need to dissect and to understand the CD133 phenotype in glioblastoma we performed a comprehensive analysis of CD133 expression and regulation in a large set of glioblastoma cell lines (n = 20) as well as in tumor xenografts. Our analysis considered alternatively spliced mRNA transcripts, different protein epitopes as well as varying sub-cellular localizations of CD133 and explored its regulation under pertinent micro-environmental conditions. CD133 mRNA and CD133 protein could be detected in all relevant types of glioblastoma cell lines. In addition, we detected frequent intracellular CD133 protein accumulations located to the ER and/or Golgi apparatus but seemingly unrelated to particular CD133 splice variants or protein epitopes. In contrast, membrane-bound expression of CD133 was restricted to tumor cells bearing the extracellular CD133 epitope AC133. Only in these cells, differentiation and oxygen levels clearly impacted on AC133 expression and to some extent also influenced CD133 mRNA and protein expression. Most importantly, however, modulation of AC133 levels could occur independently of changes in CD133 mRNA transcription, CD133 protein translation, protein retention or protein shedding. Our results suggest that the AC133 epitope, rather than CD133 mRNA or protein, mirrors malignancy-related tumor traits such as tumor differentiation and local oxygen tension levels, and thus corroborate its role as a biologically relevant cancer marker.